The Effects Of Converting Rubber Plantation Land To Oil Palm Plantations On Community Welfare In Pantai Raja Village, Perhentian Raja District, Kampar Regency - Bahruslim Bahruslim; Mulono Apriyanto; Anto Ariyanto (LPPM Universitas PGRI Sumatera Barat, 2024)
This study aims to determine the elements influencing land use transformation in Pantai Raja Village, Perhentian Raja District, Kampar Regency. The study aims to assess the effects of land function transition on community welfare. This study aims to assess the positive and negative impacts of alterations in land function. The study used a mixed-method approach, integrating quantitative and qualitative techniques to gather more comprehensive, valid, reliable, and objective data. The study comprised forty individuals, each possessing one to ten years of farming experience, with the snowball sampling method employed to ascertain the location. The study's results indicate a transition in land use from rubber agrosilviculture (Hevea brasiliensis) to oil palm agrosilviculture (Elaeis guineensis). The market price of rubber has significantly decreased from Rp 20,000 per kilogram to Rp 4,000 per kilogram. These alterations impact individuals' quality of life and their comfort levels. Weather, pricing, and agricultural practices are among the factors influencing land conversion. In Pantai Raja Village, Perhentian Raja District, Kampar Regency, the transition from rubber agriculture to oil palm production has resulted in significantly favorable outcomes, despite adverse impacts including a reduction in productive time. A reduction in burden, an augmentation of held assets, and an enhancement in family wellbeing are observed by farmers